Anticancer mechanism of troxerutin via targeting Nrf2 and NF-κB signalling pathways in hepatocarcinoma cell line. (February 2019) - Thomas, Nisha Susan; George, Kiran; Selvam, Athavan Alias Anand
Abstract: Troxerutin (TX), a bioflavonoid widely present in various fruits and vegetables, has shown to exhibit numerous pharmacological properties including anti-neoplastic and anti-cancer activities. Nrf2 and NF-κB are the key transcription factors that regulate oxidative stress and inflammation, therefore we assessed whether TX modulate these pathways and its downstream proteins in HuH-7 hepatocarcinoma cells. TX induced apoptotic cellular and nuclear changes were examined by fluorescence staining techniques, agarose gel electrophoresis and flow cytometry. Oxidative stress was determined through biochemical analysis of antioxidant enzymes and lipid peroxidation profile. The protein expressions of NF-κB and Nrf2 pathway regulators, cell proliferation markers and apoptotic pathway mediators were evaluated by performing immunoblotting, immunocytochemistry and molecular docking. Our results revealed that TX inhibits the growth of HuH-7 cells in a concentration and time-dependent manner. TX treated HuH-7 cells exhibited increased heme oxygenase (HO)-1 protein expression, augmented nuclear translocation of Nrf2, and reduced oxidative stress. Furthermore, TX suppressed the expression of IKKβ which subsequently inhibited the nuclear translocation of NF-κB (p65 subunit), and thus downregulated NF-κB mediated inflammatory responses, proliferation and cell survival. Collectively, our results indicate that TX exerts anti-cancer effect in HuH-7 hepatocarcinoma cells possibly through simultaneous regulation of the molecular signalling pathways, Nrf2 and NF-κB. Graphical abstract: Highlights: Apoptosis is the preponderant mechanism of TX induced cell death. TX causes ROS generation and exerts chromatin condensation, nuclear and DNA fragmentation. Enzymic status and lipid peroxidation profile also correlates with the cytotoxic efficacy of TX in HuH-7 cells. Mechanism of antiproliferative activity of TX involved G0/G1 phase cell cycle arrest by inhibiting PCNA and cyclin D1. TX modulates the Nrf2 and NF-κB signalling pathways and thus exerts intrinsic apoptotic cell death in HuH-7 cells.